Pelatihan teknologi media penyuluhan bagi penyuluh dan kontaktani dalam meningkatkan peran penyuluhan perkebunan karet di Kecamatan Gunung Toar Kabupaten Kuantan Singingi - Roza Yulida; Rosnita Rosnita; Yulia Andriani; Deby Kurnia (Unri Conference Series: Community Engagement, 2019)
Kuantan Singingi District is one of the districts in Riau Province that has great potential in the plantation sector, especially rubber plantations. Almost 30% of the total rubber production in Riau Province is sourced from Kuantan Singingi District. The success of this sector is inseparable from the role of counseling. The purposes of this service are; (1) Increasing extension workers 'knowledge and contactors about the classification and characteristics of agricultural extension media, (2) Increasing extension workers' knowledge and skills in selecting effective agricultural extension media; (3) Enhancing the knowledge and skills of extension workers and farmers in making agricultural extension media in the form of videos. Conduct training activities with stages of presentation and discussion with participants and the practice of making extension videos. The activity was attended by 30 participants, consisting of extension workers and rubber farmers. The activity has been able to increase the knowledge of extension workers and rubber farmers about extension media, and selection of effective extension media, as well as having skills in making extension videos. Further guidance is still ongoing so that the role of extension workers can increase.